Dr Maniac vs Robby Schwartz - Stine, R. L. (New York London Scholastic, 2008)
Robby creates his own comic strips so he can freak out his friends and family, but now his favorite character Dr. Maniac, a villain with a wicked grin and evil superpowers, is on the loose in the real world!
"Now with bonus features. Look in the back of the book for exclusive author interviews and more"--P.[iii].
410L
93417
Keywords: Comic books, strips, etc; Horror tales; Children's stories